Tiny bit lucky - Pichon, Liz. (London : Scholastic Children's Books, 2014)
"Tom Gates tells about his desire for a dog, the difficulties of enrichment week at school, his Dad's desire to take the family kiting, and Tom's band the Dogzombies who are practicing for the Rock Weekly Band Battle"--OCLC.
3-6.
3-6
Keywords: Boys -- Juvenile fiction; Families -- Juvenile fiction; School children -- Juvenile fiction; Boys -- Fiction; Family life -- Fiction; School children -- Fiction; Boys -- Fiction; Family life -- Fiction; School children -- Fiction; Diary fiction